Bioethical review of the idea of human enhancement - Selak, Marija (2010)
Bioethical review of the idea of human enhancement There are several possibilities for accomplishing the idea of overstepping the man in the biological sense. The most controversial and the prevailing ones are including the implementation of technology. It is considered that precisely with the use of technology it will be possible to overcome human biological limitations. Transhumanist movement is one of the most recognised supporters of that idea. Ethical positions in this debate are ranging from transhumanist to bio-conservative. Transhumanists argue that human enhancement technologies should be made widely available and that individuals should be able to choose which technology they would like to implement on themselves. Also, parents should have the ability to enhance their children. On the other hand, bio-conservatives are generally against biological change of human nature conducted by men. They consider that, by executing this, the idea of human dignity will be questioned. Transhumanist and bio-conservative positions will be confronted in this paper. In addition, both positions will be evaluated from the perspective of intergrative bioethics. In his paper In Defense of Posthuman Dignity transhumanist supporter Nick Bostrom argues that the notion of human dignity should be applicable on posthuman beings. Opposed to him, bio-conservatives Francis Fukuyama and Jürgen Habermas believe that purposely changing human nature has severe consequences, not only medical, but also for our understanding of law and moral. Jürgen Habermas is emphasizing this concern by arguing that this change could disable individuals to act as independent political beings.
Projekt MZOS
ENG